2004
DOI: 10.1074/jbc.m404988200
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of the Differences in Binding Properties of the Highly Related C-type Lectins DC-SIGN and L-SIGN to Lewis X Trisaccharide and Schistosoma mansoni Egg Antigens

Abstract: The dendritic cell-specific C-type lectin DC-SIGN functions as a pathogen receptor that recognizes Schistosoma mansoni egg antigens through its major glycan epitope Gal␤1,4(Fuc␣1,3)GlcNAc (Le x ). Here we report that L-SIGN, a highly related homologue of DC-SIGN found on liver sinusoidal endothelial cells, binds to S. antigens. These data demonstrate for the first time that DC-SIGN and L-SIGN differ in their carbohydrate binding profiles and will contribute to our understanding of the functional roles of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
89
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 41 publications
9
89
0
Order By: Relevance
“…From the proposed models it appears that Val 351 in DC-SIGN is close to the fucose binding site and makes a strong hydrophobic contact with CH at position 1 and 2 of fucose (38). By molecular modeling, in combination with binding studies of cell-surface expressed recombinant wild-type and mutant forms of DC-SIGN and its homologue L-SIGN (liver/lymph node-specific ICAM-3 grabbing nonintegrin), we found very similar results for the binding mode of Le X in DC-SIGN (31). Both models predict that a substituent on the 3-OH group of galactose would give a steric conflict with the side chain of Phe 313 , which is line with the results of binding studies that showed that 3Ј-sialylation or sulfation of Le X abrogates binding (43).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…From the proposed models it appears that Val 351 in DC-SIGN is close to the fucose binding site and makes a strong hydrophobic contact with CH at position 1 and 2 of fucose (38). By molecular modeling, in combination with binding studies of cell-surface expressed recombinant wild-type and mutant forms of DC-SIGN and its homologue L-SIGN (liver/lymph node-specific ICAM-3 grabbing nonintegrin), we found very similar results for the binding mode of Le X in DC-SIGN (31). Both models predict that a substituent on the 3-OH group of galactose would give a steric conflict with the side chain of Phe 313 , which is line with the results of binding studies that showed that 3Ј-sialylation or sulfation of Le X abrogates binding (43).…”
Section: Discussionsupporting
confidence: 56%
“…Recently more insight was obtained into the ability of DC-SIGN to bind fucosylated ligands (31,38). Analysis of crystals of the CRD of DC-SIGN bound to lacto-N-fucopentaose III (that comprises the Le X trisaccharide) showed that the 3-and 4-OH groups of the ␣1-3-linked fucose form coordination bonds with Ca 2ϩ in the primary binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Current data support the idea that the interaction allows HIV and HCV to be transmitted in trans to other cells, e.g., T cells and hepatocytes (4,5,15), whereas it is thought to result in direct infection by other viruses, e.g., Ebola and SARS (12,16). Recently, L-SIGN has also been shown to serve as a receptor for bacterial pathogens, e.g., Mycobacterium tuberculosis (17) and parasites such as Schistosoma mansoni (18). Because liver sinusoidal endothelial cells (LSECs) are involved in tolerance induction, the use of L-SIGN receptor as a point of entry may explain the difficulty that the immune system has in eradicating these pathogens.…”
Section: Endritic Cell (Dc)supporting
confidence: 56%
“…In this study, we highlighted the importance of CLR and TLR in the T-cell response we observed to SEA. Schistosome-derived products have been shown to bind both CLR and TLR on APC with roles identified for both TLR2 and DC-SIGN in the human and TLR2 in mice [14][15][16][17]26]. In this study, we provided evidence that in addition to its effects on DC, SEA also mediated effects directly on CD4 1 T cells, inducing surface-bound LAP and expression of the CLR DEC-205 and galectin-3 on T cells from NOD but not C57BL/6 mice ( Fig.…”
Section: Discussionmentioning
confidence: 99%